Development of a Softball Game Learning Model to Improve the Manipulative Skills of Elementary School - Risma Nana Novita; Roas Irsyada (Universitas Negeri Semarang, 2026)
Manipulative motor skills are a fundamental component of physical education learning at the elementary school level, as they support students' physical, cognitive, and social development. However, observations at Sumur 03 Public Elementary School Pati Regency, indicated that students' manipulative skills learning were still low, particularly in hitting, throwing, and catching. This study aims to develop a softball learning model through the modification of the simpleball game to improve the basic manipulative motor skills of phase C (11-12years) students Sumur 03 Public Elementary School. This study uses the Research and Development (R&D) method with the following stages: needs analysis, product design, initial product development, expert validation, small-scale field testing, product revision, and large-scale field testing. The research subjects consisted of fifth and sixth grade students. Data collection techniques included observation, manipulative skill tests (pre-test and post-test), and student response questionnaires. The data were analyzed using quantitative and qualitative descriptive analysis. The results of the learning and game expert validation showed that the Simpleball learning model was very feasible for use. The effectiveness test results showed an increase in students' basic manipulative motor skills in the aspects of hitting, throwing and catching at a distance, as well as catching a bouncing ball after the implementation of the Simpleball learning model. Student responses to the use of the Simpleball learning model also showed a very good category, which indicated high interest, involvement, and acceptance of students in learning. Based on the research results, it can be concluded that the softball learning model through the Simpleball game modification is feasible and effective for improving the basic manipulative motor skills of Phase C elementary school students.